Semiotic Analysis of œParasite Film - Angelica, Christine; Saragih, Amrin (Universitas Negeri Medan, 2021)
This study tended to find out the kinds of signs, the realizations of sign and the reasons of signs were found in Parasite film. This study used a descriptive qualitative approach. The data of the study were taken from Parasite film™s scene. The source of the data was Parasite film downloaded from Bioskop XXI. The result of the study showed that this film contained 33 semiotic signs. The data were analysed by using Peirce (1993). The result of the study found 10 icons, 17 indices and 6 symbols in Parasite film. The signs found in Parasite are realized in individual and social relations. The reason for signs used in Parasite were to identify visual signs, to show cause and effect, and to communicate metaphorical and non-metaphorical expressions.